Nutritional evaluation of some ruminant feedstuffs by in vitro gas production technique - Garg, M R; Kannan, A; Shelke, S K; Phondba, B T; Sherasia, P L (The Indian Journal of Animal Sciences, 2012)
The study was conducted to assess nutritional characteristics of some ruminant feedstuffs by using in vitro gas production technique. The commonly available feed samples of concentrates (n,18), dry (n,9) and green (n,28) roughages were collected from different parts of Gujarat. All the ground feed and fodder samples were analyzed for crude protein, ether extract, crude fiber, neutral detergent fiber, acid detergent fiber, total ash and acid insoluble ash. Metabolizable energy (ME) and total digestible nutrients (TDN) were estimated by incubating 200 mg of each of the samples with rumen mixed microbe inoculums for 24 h period, taken from fistulated buffaloes. Amongst concentrate feeds, safflower meal had lowest ME (7.21 MJ/kg DM) and TDN (48.80%) values, whereas, maize grain had highest ME (14.11 MJ/kg DM) and TDN (85.82%) values. Similarly, in dry roughages, rice husk had lowest and groundnut straw has highest ME (4.48 vs 8.93 MJ/kg DM) and TDN (22.23 vs 58.62%) values. The values of ME and TDN ranged from 5.05 to 9.15 MJ/ kg DM and 37.23 to 59.24% in green roughages, with lowest in bamboo leaves and highest in mustard Chinese cabbage. Chemical composition and energy values reported for various feed and fodders in this communication could be used for formulating ration of field animals and under farm conditions for better utilization of these commonly available feed resources.